The Influence of Financial Literacy and Interest Rate Perception on Paylater Usage Decisions for Business Capital with Risk Perception as a Moderating Variable (Study on MSMEs in Genuk District, Semarang) - Awalia Ririn Maulidina; Noni Setyorini; Rita Meiriyanti (Equivalent : Journal of Economic, Accounting and Management, 2026)
The growth of digital financing services such as Paylater in Indonesia has increased rapidly, but its utilization as a source of business capital by MSMEs actors is still relatively low. This phenomenon is evident from the low understanding of MSMEs actors regarding Paylater mechanisms, high concerns about financial risks, and negative perceptions related to interest rates and service fees. This study aims to analyze the influence of financial literacy and interest rate perception on Paylater usage decisions as business capital, as well as to examine the moderating role of risk perception on MSMEs in Genuk District, Semarang. The research method uses a quantitative approach with probability sampling technique and simple random sampling of 98 MSME respondents. Data analysis was conducted using PLS-SEM. The results show that financial literacy has a positive and significant effect on Paylater usage decisions, while interest rate perception has a negative but not significant effect. Furthermore, risk perception is proven to moderate the influence of financial literacy on Paylater usage decisions positively and significantly, indicating that MSMEs actors with high literacy and good risk awareness are more selective in utilizing Paylater services. Risk perception also moderates the influence of interest rate perception on Paylater usage decisions positively and significantly, so that MSMEs actors' sensitivity to borrowing costs increases when risk is considered. The research model has an R-square value of 0.954, indicating very good predictive capability. These findings emphasize the importance of improving financial literacy and risk education to encourage wiser financial decisions in the use of Paylater services for MSMEs.